1990
DOI: 10.1039/ft9908602701
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxygen transients in the chemistry of dioxygen at atomically clean metal surfaces: the Zn(0001)–dioxygen–ammonia system

Abstract: The exact sequence of events involving surface trapping or precursor states is not understood even for the dissociative chemisorption of simple diatomic molecules at metal surfaces. It was to search for experimental evidence for such states in the Zn(OOOl)-dioxygen system that coadsorption studies, using the ammonia molecule as a specific probe for oxygen transient states, were initiated.Using a combination of photoelectron and vibrational spectroscopies it was shown that a dioxygen-ammonia surface complex pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Oxygen adsorption on the clean surface was found to be very slow (the estimated sticking probability was *10 -3 ), yet it was enhanced to a very high value when both oxygen and ammonia were co-dosed, Fig. 8 [1,27]. It was proposed that this was due to a mobile, precursor molecular oxygen ''O 2 d-'' species, interacting with ammonia in the weakly-held state.…”
Section: Mobile Precursors Results In Increased Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen adsorption on the clean surface was found to be very slow (the estimated sticking probability was *10 -3 ), yet it was enhanced to a very high value when both oxygen and ammonia were co-dosed, Fig. 8 [1,27]. It was proposed that this was due to a mobile, precursor molecular oxygen ''O 2 d-'' species, interacting with ammonia in the weakly-held state.…”
Section: Mobile Precursors Results In Increased Surfacementioning
confidence: 99%
“…Roberts et al [1,[27][28][29] have reported surface reactions which are of an inverse type, that is, oxygen adsorption itself is enhanced via the precursor state. In these experiments oxygen was not pre-adsorbed, but precursors are pivotal for high reaction rates to be seen.…”
Section: Mobile Precursors Results In Increased Surfacementioning
confidence: 99%
“…Since at the sp metals Zn(0001) and Ag(111), dioxygen bond cleavage is ''slow'' there is a kinetic window to [10][11][12] with decreasing temperature (Fig. 2) and also as the ratio NH 3 :O 2 increases.…”
Section: Activation Of Dioxygen By Coadsorbatesmentioning
confidence: 98%
“…The 'catalytic' role of the ammonia in dioxygen bond cleavage is highlighted by comparison with pure dioxygen at 200 K. Adapted from Ref. [44] with permission from the Royal Society of Chemistry …”
Section: Discussionmentioning
confidence: 99%